Religious Freedom Theology in Q.S. Al-Baqarah (2): 256 and Its Implications for Interfaith Harmony in North Sulawesi: Teologi Kebebasan Beragama dalam Q.S. Al-Baqarah: 256 dan Relevansinya Terhadap Harmoni Lintas Iman di Sulawesi Utara - Basri Saenong; Achmad Abubakar; Mardan Mardan (Institut Agama Islam Negeri Kerinci, 2025)
This article aims to analyze the principle of religious freedom in the Qur'an, focusing on Q.S. Al-Baqarah verse 256, and its relevance as a theological basis for interfaith harmony in North Sulawesi. This study uses a library research method with a qualitative-descriptive approach based on thematic interpretation (mauhdu'i). The research data sources include primary data consisting of verses from the Qur'an, classical and contemporary interpretations. Sociological analysis is used as an interpretive approach, utilizing the theories of Peter L. Berger and José Casanova to examine the relationship between theological principles and social practices of diversity. The results of the study show that the verse